Antimicrobial potential, GC-MS analysis, and molecular docking studies of Pogostemon benghalensis leaf extract - Kashyap, Bhaswati; Das, Siddhartha Sankar; Sharma, Dipjyoti; Bora, Nilutpal Sharma; Gam, Sameeran; Dutta, Koushik Nandan (Creative Pharma Assent, 2025)
Background: Pogostemon benghalensis has several medicinal uses in Northeast India, including wound healing activity. Currently, no molecular modeling research has examined the antimicrobial potential of its phytoconstituents. This molecular docking research identifies bioactive chemicals and evaluates their antibacterial properties. Methodology: Phytochemical screening and in vitro antibacterial tests were performed on a crude ethyl acetate extract of Pogostemon benghalensis leaves. After GC-MS analysis revealed the phytoconstituents, in-silico molecular docking was performed against the dihydrofolate reductase (DHFR) enzymes of Escherichia coli and Staphylococcus aureus. Results and discussion: The crude ethyl acetate extract of Pogostemon benghalensis leaves included alkaloids, carbohydrates, flavonoids, glycosides, tannins, and phenolic compounds. The extract also demonstrated potent in vitro antibacterial activity against E. coli and S. aureus. GC-MS data demonstrated that Phytol was the most abundant compound (53.72%) followed by Oxirane, dodecyl (13.51%.). Molecular docking studies demonstrated identified compounds have high binding affinity (BA) to the bacterial DHFR enzyme. Notable compounds are Androst-5-ene-3,19-diol, 3-acetate (3 β) with -7.4 kcal/mol BA against E. coli DHFR and -10.1kcal/mol against S. aureus DHFR; Retinol acetate with -8.7 kcal/mol BA against E. coli DHFR and Phytol with -6.5 kcal/mol BA against E. coli DHFR and -6.7 kcal/mol BA for S. aureus DHFR respectively. Conclusion: The results show that Pogostemon benghalensis contains valuable bioactive compounds with high antibacterial activity which further validates the use of this plant as a wound healing medication. However, further in vivo experimental validation of these results and their toxicological implications are required.